Developmental Trends in Sexual Attraction Among Puerto Rican Early Adolescents in Two Contexts. Issue 3 (20th July 2019) - Elkington, Katherine S.; Wainberg, Milton L.; Ramos‐Olazagasti, Maria; Chen, Chen; Ortin, Ana; Canino, Glorisa J.; Bird, Hector R.; Duarte, Cristiane S.
Abstract : Sexual attraction (SA), the earliest stage of sexual orientation, is scarcely studied. This prospective study examined, over 3 years, prevalence, changes in SA, and the role of context, among 946 Puerto Rican youth, aged 11–13 years at initial assessment in the South Bronx (SBx), New York City, and Puerto Rico (PR). Overall, 98.1% of boys and 95.3% of girls reported opposite‐sex only SA at some point, whereas 13.8% of girls and 12.0% of boys reported any‐same SA. Opposite‐sex only SA increased over time, whereas other SAs decreased except for any same‐sex SA among SBx girls. Girls in the SBx and younger youth in PR reported more any same‐sex SA. Context and culture may play a role in the developmental trajectories of adolescents' SA.